2013
DOI: 10.1016/j.ajog.2013.05.050
|View full text |Cite
|
Sign up to set email alerts
|

Clinical morbidities, trends, and demographics of eclampsia: a population-based study

Abstract: OBJECTIVE We sought to identify trends, demographics, and pre-pregnancy and peripartum morbidities of eclampsia in California. STUDY DESIGN We identified cases of eclampsia by International Classification of Diseases, Ninth Revision code using California health discharge data from 2001 through 2007. Cases with missing race/ethnicity as well as age <15 years or >55 years were excluded. Among the remaining cases, patients with eclampsia (n = 1888) were compared against those without (n = 2,768,983). Adjustment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 22 publications
(30 reference statements)
1
50
1
2
Order By: Relevance
“…13 Our study also proved that eclampsia was more common at an early age which is also proved by Fong et al, which states that eclampsia has a bimodal distribution which peaks in youngest and oldest age group. 14 Jaiswar et al, observed the mean LDH level in control was 278.33±119.25 IU/L, in mild preeclampsia was 400.45±145.21 IU/L, severe preeclampsia was 646.95±401.64…”
Section: Discussionmentioning
confidence: 99%
“…13 Our study also proved that eclampsia was more common at an early age which is also proved by Fong et al, which states that eclampsia has a bimodal distribution which peaks in youngest and oldest age group. 14 Jaiswar et al, observed the mean LDH level in control was 278.33±119.25 IU/L, in mild preeclampsia was 400.45±145.21 IU/L, severe preeclampsia was 646.95±401.64…”
Section: Discussionmentioning
confidence: 99%
“…32 The prevalence of preeclampsia in many of these studies may be underestimated because preeclampsia is often underreported and misclassified and because the presence of preeclampsia is often used as an exclusion criterion from the diagnosis of PPCM. PPCM is also frequently found in association with eclampsia, with an odds ratio of 12.9 in a California population study of 1888 patients with eclampsia 33 and 27.9 in the multistate hospital discharge study of PPCM cases noted above. 18 It is important to realize that preeclampsia or pregnancyinduced hypertension can also trigger pulmonary edema in the absence of PPCM.…”
Section: Preeclampsia and Hypertensionmentioning
confidence: 99%
“…[12][13][14][15] The incidence of eclampsia in developed countries is estimated to about 5-7/10,000 deliveries whereas in developing countries varies widely 1 case/100 to 1 case/1700 pregnancies. 5,16,17 Majority of the patients are of primigravida (78.8%) in their early reproductive age <25 years (60.4%) with unsupervised pregnancy ( in their antenatal period and referred cases (76.8%). These data's are comparable to other studies.…”
Section: Discussionmentioning
confidence: 99%
“…PPH (8.4%), APH (6.8%), ARF (13.2%), Hypertensive retinal changes (5.6%), pulmonary oedema (4.4%), HELLP syndrome (4.4%), DIC (2.0%), Septicaemia (2.8%), prolonged unconsciousness (1.2%) and death (11.2%) similar to study of Pradeep MR et al, Sunita TH et al and the study conducted in Nigeria but case fatality rate (11.2%) is very high in comparison to other Indian studies as well as from developed countries because of being a tribal area there are limited health resources and there is delay in reaching the tertiary care centre as most of the cases (52/84) developing complications having large interval (>12 hrs) from onset of convulsion to delivery which is a significant factor determining the maternal as well as perinatal outcome. 5,[8][9][10]12,18,19,[23][24][25] Most common cause of maternal death in our study is pulmonary oedema (21.4%) because of limited facility of intensive care unit, ventilator as well as large drainage area of poor tribal population. Other deaths are due to HELLP syndrome, ARF, Septicaemia, Cerebral haemorrhage and multiorgan failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation